IDE DAN PRAKSIS TOLERANSI Pengalaman Eropa Pasca-Reformasi Martin Luther - Eddy Kristiyanto (Studia Philosophica et Theologica, 2002)
One of theses that would be presented here in this article is within the historiography of the modern era of religious tolerance the Protestant Reformation era has always been considered of paramount important for the developments which led to the achievement of a liberal and tolerant society. The history shows, however, that the first century of the Reformation was followed by the intolerence, and some nations like Germany, France, England put into practice the political, economic interets which corelatted with religious belief. The break-up of the near monolithic structure of medieval Western Christianity for the first time presented contemporary lay and ecclesiastical rulers with the practical problem of how to deal with religious plurality. The aspects of religious toleration, such as freedom of conscience and freedom of worship, are something new. This article presents the efforts of Western Christians to give the solution.